Subjective Experience of Episodic Memory and Metacognition: A Neurodevelopmental Approach - Souchay, Celine; Guillery-Girard, Berengere; Pauly-Takacs, Katalin; Wojcik, Dominika Z.; Eustache, Francis (Frontiers in Behavioral Neuroscience, 2013)
Episodic retrieval is characterized by the subjective experience of remembering. This experience enables the co-ordination of memory retrieval processes and can be acted on metacognitively. In successful retrieval, the feeling of remembering may be accompanied by recall of important contextual information. On the other hand, when people fail (or struggle) to retrieve information, other feelings, thoughts, and information may come to mind. In this review, we examine the subjective and metacognitive basis of episodic memory function from a neurodevelopmental perspective, looking at recollection paradigms (such as source memory, and the report of recollective experience) and metacognitive paradigms such as the feeling of knowing). We start by considering healthy development, and provide a brief review of the development of episodic memory, with a particular focus on the ability of children to report first-person experiences of remembering. We then consider neurodevelopmental disorders (NDDs) such as amnesia acquired in infancy, autism, Williams syndrome, Down syndrome, or 22q11.2 deletion syndrome. This review shows that different episodic processes develop at different rates, and that across a broad set of different NDDs there are various types of episodic memory impairment, each with possibly a different character. This literature is in agreement with the idea that episodic memory is a multifaceted process.